2017
DOI: 10.1158/0008-5472.can-17-0580
|View full text |Cite
|
Sign up to set email alerts
|

TumorMap: Exploring the Molecular Similarities of Cancer Samples in an Interactive Portal

Abstract: Vast amounts of molecular data are being collected on tumor samples, which provide unique opportunities for discovering trends within and between cancer subtypes. Such cross-cancer analyses require computational methods that enable intuitive and interactive browsing of thousands of samples based on their molecular similarity. We created a portal called TumorMap to assist in exploration and statistical interrogation of high-dimensional complex “omics” data in an interactive and easily interpretable way. In the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 12 publications
1
66
0
Order By: Relevance
“…iC was optimized using k-means for 28 major clusters, and visualized by TM. The latent variables were used to generate a TM layout of the samples (Newton et al, 2017). The TM layout was computed using the Euclidean similarity between each pair of samples in the iC latent space.…”
Section: Star*methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…iC was optimized using k-means for 28 major clusters, and visualized by TM. The latent variables were used to generate a TM layout of the samples (Newton et al, 2017). The TM layout was computed using the Euclidean similarity between each pair of samples in the iC latent space.…”
Section: Star*methodsmentioning
confidence: 99%
“…We used TumorMap (TM) (Newton et al, 2017), an interactive visualization and analysis portal, coupled with integrated Cluster (iCluster [iC]) (Shen et al, 2009), and we found high overlap with original histopathologic classifications of SCC. Further, these tools uncovered broader and subtype-related genetic and epigenetic alterations that distinguish SCCs from other cancers and from one another.…”
Section: Introductionmentioning
confidence: 99%
“…We used the UCSC TumorMap (Newton et al 2017) to visualize clusters of expression profiles across PDX histologies (Figure 5A). We observed clear separation among unrelated histologies and overlapping clustering among related histologies.…”
Section: Resultsmentioning
confidence: 99%
“…We then compared the clustering patterns across MYCN-NA neuroblastoma, osteosarcoma, Ewing sarcoma, embryonal rhabdomyosarcoma, alveolar rhabdomyosarcoma, and synovial sarcoma. We applied the TumorMap dimensionality reduction method [5] to visualize clustering of the full small blue round cell tumor gene expression matrix. We then applied the hydra framework to explore expression variation within each disease.…”
Section: Small Blue Round Cell Tumor Analysismentioning
confidence: 99%
“…Large cancer sequencing projects, including The Cancer Genome Atlas (TCGA) and Therapeutically Applicable Research to Generate Effective Treatments (TARGET), have facilitated the development of cancer gene expression compendia [1][2][3][4][5][6], but these compendia often lack expression data from corresponding normal tissue. Without the normal comparator, Hoadley et al (2018) found that cell-of-origin signals drive integrative clustering of TCGA data.…”
Section: Introductionmentioning
confidence: 99%